Later Risk of Wheezing/Asthma and Allergy in Offspring of 2 Vitamin D (VitD) Pregnancy Cohorts: Post Hoc Analysis. (29th May 2020) - Wagner, Carol; Ebeling, Myla; Shary, Judy; Baatz, John; Newton, Danforth; Weiss, Scott; Hawrylowicz, Catherine; Hollis, Bruce
Abstract: Objectives: Maternal vitD deficiency as defined by circulating 25(OH)D concentration is linked with certain adverse pregnancy outcomes (e.g., preterm birth) and childhood outcomes (e.g., asthma), with the effect seemingly more pronounced if deficiency occurs earlier in pregnancy. OBJ: Assess the long-term effect of maternal and neonatal vitD status on later risk of childhood allergy, wheezing and/or asthma to 4 yrs. It was hypothesized that deficiency earlier in pregnancy would have a significant effect on risk that would continue during pregnancy. Methods: In this follow-up post hoc analysis of women and their offspring enrolled in 1 of 2 pregnancy vitD supplementation trials (NICHD, n  = 348 and Kellogg Foundation, n  = 298), women were randomized to either 400, 2000 or 4000 IU vitD/day (NICHD) at 12–16 wks' or 400 or 4400 IU/day at 10–14 wks' (Kellogg). Baseline then monthly 25(OH)D concentration as the primary outcome in both studies and as the indicator of vitD status was measured by RIA until delivery. Neonatal vitD status was measured in cord blood. Follow-up data on the offspring were available through 4 yrs using an EMR with ICD-9 and 10 codes for eczema, wheezing and/or asthma. Student's t-test was used to analyze differences in mean 25(OH)D and eczema, wheezing, and asthma. Chi-square analyses were used to test for differences in incidence of 25(OH)D below 20, 30, and 40 and eczema, wheezing, and asthma. Results: In NICHD Pregnancy, 326/348 (93.7%) offspring had EMR data available: 48 (14.7%) had eczema; 32 (9.8%) had wheezing; and 48 (14.7%) had asthma. In Kellogg Pregnancy, 205/298 (68.8%) had EMR data available; 36 (17.6%) had eczema; 14 (6.8%) had wheezing; and 10 (4.9%) had asthma. Maternal baseline 25(OH)D < 30 ng/mL was associated with eczema ( P  = 0.024) and asthma ( P  = 0.035) by age 4 yrs. Neonatal 25(OH)D was inversely associated with eczema ( P  = 0.01) and asthma by age 4 ( P  = 0.0012). When dichotomized, neonates with 25(OH)D < 20 ng/mL had a significantly higher risk of eczema ( P  = 0.02) and asthma ( P  = 0.004) and those below 40 ng/mL had a higher risk of eczema ( P  = 0.03). Conclusions: In this combined cohort of pregnant women and their offspring, both maternal and neonatal vitD status were associated with later allergy, wheezing and asthma risk. Efforts to improve maternal vitD status may have later significant consequences on childhood health outcomes. Funding Sources: NIH/NICHD/NCATS.